Understanding Generation Z Consumer Behavior and Perceptions Towards Organic Products : Implications for Private Labels - Weston, Emily Gabriela (2025)
This thesis explores the perceptions and purchasing behaviour of Generation Z consumers in the Czech Republic towards organic food, with a particular focus on organic private labels. While both organic food and private labels have been examined in prior research, their intersection, especially in the Czech context and among younger consumers, remains underexplored. To address this gap, the study combines semi-structured interviews and a quantitative survey. The qualitative phase verified and uncovered key associations, motivations, and barriers, which informed the survey design. The quantitative phase tested an extended Theory of Planned Behaviour model and revealed that perceived quality, environmental concern, and trust significantly influence attitudes, which in turn predict purchase intention and behaviour. Further findings highlight that health and quality are the most common motivations for buying organic food, while high price is the primary barrier to more frequent purchasing. Among organic private labels, Nature’s Promise emerged as the most recognised and purchased brand. Key drivers of organic private label purchases include in-store availability and positive prior experience, along with greater affordability when compared to national brands. While marketing-related factors were not explicitly tested, the findings suggest that brand awareness, retailer image, and overall brand image play an important role in shaping consumer behaviour. The research contributes to the literature in a novel context, while also providing practical recommendations for retailers and marketers on strengthening organic private label strategies and engagement with Generation Z.